Normatização da abertura de ligas acadêmicas: a experiência da Faculdade de Medicina de Botucatu - Hamamoto Filho, Pedro Tadao [UNESP]; Bôas, Paulo José Fortes Villas [UNESP]; Corrêa, Fabiane Gomes [UNESP]; Muñoz, Gabriela Ortega Cisternas [UNESP]; Zaba, Michelle [UNESP]; Venditti, Vinicius Cunha [UNESP]; Schellini,Silvana Artioli [UNESP] (FapUNIFESP (SciELO), 2010)
Student leagues have been created by medical students all across Brazil. Accepted as extracurricular university extension activities, the leagues have produced both benefits and risks for medical training. Student leagues thus need to be rationalized, with the aim of improving their activities. This report describes the regulation adopted by the Botucatu School of Medicine (Universidade Estadual Paulista, FMB/UNESP), framed within a discussion of the importance of such leagues as extracurricular activities and the potential harm they can cause to medical training. The regulation contains procedural guidelines and a set of criteria for the evaluation of proposals to create new leagues. The criteria assess the proposal’s relevance, objectives, planned management model, and training ideology. The use of these guidelines has allowed the development of projects for new leagues and triggered more in-depth reflection in the school on the role of student leagues.

Acriação de ligas acadêmicas por estudantes de Medicina tem ocorrido em todo o Brasil. Aceitas como atividades extracurriculares de extensão universitária, as ligas trazem tanto benefícios como riscos à formação médica. Assim, a abertura de ligas deveria ser racionalizada, visando ao aperfeiçoamento de suas atividades. Neste relato, descrevemos a normatização adotada na Faculdade de Medicina de Botucatu – Universidade Estadual Paulista (FMB/Unesp), contextualizando-a numa discussão sobre a importância das ligas como atividades extracurriculares e os prejuí- zos que podem trazer à formação médica. A normatização contém orientações processuais e um conjunto de critérios para avaliação dos projetos de abertura de novas ligas. Os critérios avaliam a relevância da proposta, os objetivos, o modelo de gestão planejado e a ideologia da formação. A utilização destas diretrizes tem capacitado o desenvolvimento de projetos de novas ligas e desencadeado na escola o aprofundamento de reflexões sobre a função de ligas acadêmicas.
Regulation of student leagues: the experience at the Botucatu School of Medicine
Keywords: Education, medical; Community institutional relations; Students, medical; Educação médica; Relações comunidade-instituição; Estudantes de medicina